Optimal design of hierarchical grid-stiffened cylindrical shell structures based on linear buckling and nonlinear collapse analyses - Zhao, Yunong; Chen, Mingji; Yang, Fan; Zhang, Ling; Fang, Daining (Thin-walled structures, 2017)
This paper considers the optimization of a grid-stiffened cylindrical shell with weld and transition lands. A surrogate-based optimization framework incorporating the multi-island genetic algorithm (MIGA) is adopted based on linear eigenvalue buckling analysis (LEBA) and nonlinear implicit analysis (NIA). A novel hierarchical grid design is proposed to avoid undesired local buckling. In addition, the results indicate that the optimization based on LEBA is intended primarily to avoid local failure rather than structure collapse, and thereby deviates from the optimal design. In contrast, the optimization based on NIA yields designs that are closer to the optimal design for engineering application. •An integral and efficient analysis and optimization framework for the design of stiffened cylindrical shells is presented.•A novel hierarchical grid design is proposed to avoid undesired local buckling.•Optimization framework based on nonlinear implicit analysis is more suitable for the design of complex structures.